Sexual stings in scorpions - knock-out drug or love potion? - Reitsema-Wang, Yuqi; Simone, Yuri; Herzig, Volker; Jenner, Ronald A.; Lüddecke, Tim; Krämer, Jonas (Frontiers in Arachnid Science, 2025)
Conspecific male to female envenomation, though rare, has been documented across venomous taxa. While traditionally interpreted as a coercive mating strategy to enhance male reproductive success and to avoid cannibalism, this explanation may not fully account for the behaviour in scorpions, which exhibit minor sexual size dimorphism and complex courtship rituals. This review explores the possibly multifaceted roles of sexual stinging in scorpions. We highlight potential adaptive strategies, such as venom metering and compositional plasticity, that allow males to subdue females without causing lethal harm. We discuss hypotheses on the evolution of sexual stings, ranging from sexual coercion to chemical seduction and cooperative signalling. Finally, we propose future research directions, including comparative venomics, behavioural assays, and ecological studies, to shed light on the selective pressures that shape this enigmatic behaviour. By integrating insights from physiology, ecology, and evolution, this review advances our understanding of sexual envenomation as a dynamic interplay between conflict and cooperation in scorpion reproductive strategies.